THE POLA KOMUNIKASI SISWA TULI MENGGUNAKAN SIBI DI SLBN BADEGAN - Mayrina Eka Prasetyo Budi; Ananda Erliyana Putri (Proceeding of Conference on Strengthening Islamic Studies in The Digital Era, 2023)
ign language is the main media in the communication process for the deaf people. The sign language used by the deaf people is called SIBI (Indonesian Signing System) which is the official sign language of Indonesia. SIBI represents Indonesian spoken grammar into sign language. The purpose of this study is, first, to describe how the communication patterns of deaf students use SIBI at SLBN Badegan. Second, to describe how the teacher’s communication patterns with deaf students use SIBI at SLBN Badegan. Researchers use a qualitative approach to phenomenology. Sources of data obtained through observation, interviews, and documentation. In conducting data processing, researchers used the Miles and Habermas model which included: reduction, data presentation, and conclusions. The results of this study indicate that, first, the communication patterns of deaf students fully used SIBI sign language. The types of communication patterns of deaf students in communication with their friends are non-verbal primary communication patterns. Second, the teacher’s communication pattern with deaf students uses a total (comtal) communication approach which is a combination of the use of SIBI sign language and the use of oral (verbal communication). The form of the teacher’s communication pattern with deaf students is a communication pattern with a star structure.